Edukasi Kepatuhan Pajak Bagi Pelaku UMKM Untuk Mendorong Kemandirian Dan Pertumbuhan Ekonomi Lokal - Islamiah Kamil; Yolifiandri Yolifiandri; Erfiana Wahyuningsih (Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are facing challenges due to a lack of understanding of tax obligations and limited access to information. The urgency of this activity lies in the need to improve tax literacy so that MSMEs can properly fulfill their tax obligations and contribute to state revenue and local economic growth. The objective of this activity was to provide education and outreach regarding the importance of tax compliance, the types and rates of taxes applicable to MSMEs, and an understanding of tax reporting procedures in accordance with applicable regulations. The activity was held at Graha Wiranesia, Pasar Minggu, South Jakarta, involving 21 MSMEs from the industrial and culinary sectors. The implementation method used an interactive lecture approach, discussion, and question-and-answer sessions to strengthen participants' understanding of tax concepts. This approach was designed to facilitate participants' understanding of the material without having to go through technical simulations. The targeted outcome of this activity was increased participant knowledge and awareness of tax compliance. This program is expected to be the first step in building a culture of tax compliance and supporting the financial independence of MSMEs to strengthen regional economic growth.